Core knowledge translation competencies: a scoping review - Anastasia A. Mallidou; Pat Atherton; Liza Chan; Noreen Frisch; Stephanie Glegg; Gayle Scarrow (BMC, 2018)
Abstract Background Knowledge translation (KT) is the broad range of activities aimed at supporting the use of research findings leading to evidence-based practice (EBP) and policy. Recommendations have been made that capacity building efforts be established to support individuals to enact KT. In this study, we summarized existing knowledge on KT competencies to provide a foundation for such capacity building efforts and to inform policy and research. Our research questions were "What are the core KT competencies needed in the health sector?" and "What are the interventions and strategies to teach and reinforce those competencies?" Methods We used a scoping review approach and an integrated KT process by involving an Advisory Group of diverse stakeholders. We searched seven health and interdisciplinary electronic databases and grey literature sources for materials published from 2003 to 2017 in English language only. Empirical and theoretical publications in health that examined KT competencies were retrieved, reviewed, and synthesized. Results Overall, 1171 publications were retrieved; 137 were fully reviewed; and 15 empirical and six conceptual academic, and 52 grey literature publications were included and synthesized in this scoping review. From both the academic and grey literature, we categorized 19 KT core competencies into knowledge, skills, or attitudes; and identified commonly used interventions and strategies to enhance KT competencies such as education, organizational support and hands-on training. Conclusions These initial core KT competencies for individuals provide implications for education, policy, knowledge brokering, and future research, and on the need for future evaluation of the KT competencies presented. We also discuss the essential role of organizational support and culture for successful KT activities/practice.